(untitled) (Al-Academy, 2016)
The phenotypic characteristics in the interior spaces are seeing the result of the ability of the designer in his handling of the vocabulary and the elements to deliver a specific meaning for the recipient , and is working to stir up the receiver and make it effective in the process of perception of space. So the theme of the role of phenotypic characteristics is of great significance in the process of analyzing spaces to reach the goal of the main idea , and show those qualities through relationships design in terms of shape, color and texture ... etc. , to reach also designs more beautiful , and creating an internal environment , creative and continuous with its external environment , Hence the importance of research in that it tries to provide indicators tell us to know the effective role of phenotypic traits , because it is one of the important means in practical new design . It is all of the above we can summarize the research problem in a few studies of clear and direct that reveal the role of phenotypic characteristics between inside and outside , being one of the most important means of design , which deals with the designer to reach its destination , as well as the role of that system to highlight the inter-relationship with the elements of interior design , the objective of this research has represented access to determine the role of phenotypic characteristics at the Title ( performative and aesthetic ). The theoretical framework of the research has included the study of several aspects of the study included all of the concept of beauty and aesthetic experience of taste and aesthetic judgment aesthetic in enhancing qualities phenotypic expression of the inner space and its mechanisms , and achieved through relations aesthetic capable of enriching the aesthetic side through ( unity and diversity , balance and proportion and rhythm ) through the visual elements ( lighting , color , texture ) , and after the completion of the theoretical framework has been drawn set of indicators and analysis of the sample and Achtkhalas set of findings and conclusions , and finally the list of sources .